A Retrospective Clinico-Pathological Analysis with Review of Literature of Oral and Cervical Lympho-Epithelial Cysts from a Pathological Perspective - Lucille Trottet; Primali Rukmal Jayasooriya; Udari W. A. M. Lakshika Abeyasinghe; Ranjit B. R. Nihal Mendis; Tommaso Lombardi (Applied Sciences, 2022)
Oral and cervical lympho-epthelial cysts (LECs) are uncommon lesions with histopathological similarities. The aim of the study is to present clinico-pathological characteristics of oral and cervical LECs with a review of literature in order to create awareness on this uncommon entity. Eighteen new cases of oral and cervical LECs obtained from the archives of the University of Peradeniya and University of Geneva were used for the clinico-pathological analysis. The average age at diagnosis of 7 oral and 11 cervical LECs were 40 and 36 years, respectively. Both showed a female predilection (male:female ratio at 3:4 and 4:7, respectively). The only difference was found in the size of the lesions with oral LECs being significantly smaller than cervical LECs (0.9 cm vs. 4.6 cm). LECs may clinically resemble neoplasms (4/18), including malignancies (1/11 in the present series). None of the 18 LECs recurred following surgical removal. The literature-review-based analysis of 514 oral LECs confirms that the lesions are observed predominantly in adults in 4th–5th decades of life and are relatively small lesions of less than 2 cm in diameter. Oral LECs were found to occur predominantly in the tongue and floor of the mouth, similar to 88% of lesions in literature. In conclusion, oral and cervical LECs are two histologically similar cysts that occur in two distinct sites. The literature review supports the information observed in our study with respect to age of occurrence, site predilections, and size. Cervical LECs, particularly the ones that occur in the parotid region, may require further investigations to exclude BLEL of parotid gland, which occur in HIV infected patients.